Relationship between Attachment Dimensions and Emotion Regulation among Adolescents - Khadeejah Iqbal (Journal of Management Practices, Humanities and Social Sciences, 2024)
Early experiences with attachment figures significantly influence the development of emotional regulation, which plays a crucial role during the transition from childhood to adolescence—a period marked by rapid psychological and physiological changes. This research aimed to explore the relationship between attachment dimensions and the regulation of three types of emotions—anger, sadness, and fear- among children and early adolescents aged 10-16. A cross-sectional study design was employed. The sample consisted of 312 students (140 males and 172 females) from government and private schools in Islamabad, with a mean age of 13.8 years (SD=1.57). The